Assistance in Administrative Transformation Through (One Stop Service) to Create an Independent Village - Eriyana, Rina; Desiyanto, Jatim; Naim, Mahin Ainun (Universitas Tanjungpura, 2024)
In the current era of globalization, advances in information technology are developing very rapidly. This affects every existing agency, both village governments and regional governments. Moreover, village governments urgently need administrative transformation so that services to the community can be more effective and efficient. One effort to transform village administration is to implement one-stop integrated village services (one-stop service). This service activity aims to assist the village government and the people of Ragung Village in implementing one-stop integrated village services, so that an independent village can be realized. The method used is a mentoring method through the stages of forming an executive committee, training, and implementation. The results of this service activity show that the implementation of one-stop integrated village services in Ragung Village has gone well. The community can handle various administrative needs in one place, making the time and costs required for their administrative needs more efficient. Based on the results of this service activity, it can be concluded that implementing one-stop integrated village services is an effective effort to improve the quality of village administration services. One-stop integrated village services can provide benefits for the community, village government, and regional government. Additionally, community satisfaction with village administration services has also increased. In conclusion, implementing one-stop integrated village services is an effective effort to improve the quality of village administration services.